2022
DOI: 10.1371/journal.pone.0263169
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perception towards educational environment in governmental Universities of Southwest Ethiopia: A qualitative study

Abstract: Background Educational environment refers to the diverse physical facilities, the clinical settings where students learn, the design and delivery of the curriculum, and involve the skills, and attitudes of the teachers. Due to various undesirable aspects of the educational environment, students often do not attain the expected professional standard of nursing care. There is limited evidence on students’ perception of their educational environment in Ethiopia, particularly in the study area. Thus, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Other factors such as gender, age, socioeconomic status and the individual preferences appeared as negatively predicting the probability of the nursing students on clinical placement in the rural clinic facilities returning in the future if offered employment. Related studies on brain drain issues in Nigeria and other developing nations have indicated the above mentioned factors, 55 - 59 but the present study deepened the knowledge by focusing on the rural clinic facilities and the future nurses. Sustainability of rural health in the developing nations such as in southeast Nigeria is much dependent on the process of training the health workers in the institutions of higher learning, which includes familiarity with the rural clinic facilities.…”
Section: Discussionmentioning
confidence: 66%
“…Other factors such as gender, age, socioeconomic status and the individual preferences appeared as negatively predicting the probability of the nursing students on clinical placement in the rural clinic facilities returning in the future if offered employment. Related studies on brain drain issues in Nigeria and other developing nations have indicated the above mentioned factors, 55 - 59 but the present study deepened the knowledge by focusing on the rural clinic facilities and the future nurses. Sustainability of rural health in the developing nations such as in southeast Nigeria is much dependent on the process of training the health workers in the institutions of higher learning, which includes familiarity with the rural clinic facilities.…”
Section: Discussionmentioning
confidence: 66%
“…One factor where students in clinic placements expressed more challenges to their learning was with housing and transportation which is often out of the control of individual students or difficult for universities to negotiate. Housing and transportation for students CLE is often a challenge, especially in countries with limited infrastructure and resources, and has been shown to negatively impact students’ clinical learning experiences [ 36 , 37 ]. As Sierra Leone and other countries are interested in scaling up the number of midwives trained, issues of transportation and housing are important issues to address to ensure that students feel supported at any clinical placement site.…”
Section: Discussionmentioning
confidence: 99%
“…Some graduated from junior high school, some from elementary school, and some did not pass (class III and then dropped out). There are various reasons for the educational background, including educational conditions, family economic conditions, and individual awareness of school, both parents and children (Fego et al, 2022).…”
Section: Parental Education In Indonesiamentioning
confidence: 99%